2018
DOI: 10.1002/asia.201800437
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Evidence of Two Competing Thermal Electrocyclization Pathways for Vinylheptafulvene

Abstract: The thermal electrocyclic ring-closure reaction of vinylheptafulvene (VHF) to form dihydroazulene (DHA) is elucidated herein by using DFT and H NMR spectroscopy. Two different transition states were found computationally; one corresponds to a disrotatory pathway, which is allowed according to the Woodward-Hoffmann selection rules, whereas the other corresponds to a conrotatory pathway. The conrotatory pathway is found to be zwitterionic in the transition state, whereas the disrotatory transition state varies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…There is no doubt that the trans-isomer is favored in the reactions, but in all cases we assume both isomers are formed, also in those cases where mixed fractions were not isolated, since we cannot exclude that the cis-isomer is simply lost during the tedious work-up. As we have shown previously, [19,20] however, subject- ing a pure diastereoisomer to light-induced ringopening in MeCN will generate both diastereoisomers in the thermal back-reaction. The switching studies described below were in each case carried out starting with the pure diastereoisomer.…”
Section: Synthesismentioning
confidence: 53%
See 1 more Smart Citation
“…There is no doubt that the trans-isomer is favored in the reactions, but in all cases we assume both isomers are formed, also in those cases where mixed fractions were not isolated, since we cannot exclude that the cis-isomer is simply lost during the tedious work-up. As we have shown previously, [19,20] however, subject- ing a pure diastereoisomer to light-induced ringopening in MeCN will generate both diastereoisomers in the thermal back-reaction. The switching studies described below were in each case carried out starting with the pure diastereoisomer.…”
Section: Synthesismentioning
confidence: 53%
“…Introducing a substituent at position C(1) generates a second stereocenter, in addition to the one at position C(8a), and the DHA can hence exist as diastereoisomers. By studying a derivative with a benzothiazole group [20] (Scheme 2; R = H -1a/1b), we found that the ratio of diastereoisomers formed by VHF ring closure depended on the solvent polarityin a nonpolar solvent, the product from a disrotatory ring closure (Woodward-Hoffmann allowed) dominated, while the product from a conrotatory ring closure was formed in the same amount as the other diastereoisomer in a polar solvent like MeCN. For the parent structure shown in Scheme 1, the conrotatory pathway was calculated to have the lowest Gibbs free energy of activation no matter the solvent; the transition state structures from both pathways had significant zwitterionic characters, and they were influenced to quite similar degrees to changes in solvent polarity.…”
Section: Introductionmentioning
confidence: 99%
“…described the surface for model systems with no nitrile groups on the C1‐position, showing a conical intersection sloping on the DHA side. Other groups have estimated the surfaces, but a full description of the excited state surfaces for a non‐model system has yet to be completed.…”
Section: Discussionmentioning
confidence: 99%
“…For the transition states (TSs) of the electrocyclic ring‐opening/closure, the imaginary frequencies were confirmed to correspond to the C1‐C8a bond‐breaking/forming reaction coordinate (see atom numbering in Figure ). In the ground state, the TS reported is the energetically lowest of the two electrocyclic pathways . The Gibbs free energy calculations include the zero‐point vibrational energy and thermal contributions evaluated at a temperature of 298.15 K and a pressure of 1.00 atm.…”
Section: Methods Sectionmentioning
confidence: 99%
“…Ah alf-life for 13-11 of about 3min was determined at 25 8C, and af ew light-heatc ycles were performed. Resultss howed ad ecrease of 1% per cycle in absorbance in the UV/Vis absorptions pectra of both 13-00 and 13-11 ( Figure 6), which could be connected to fatigue or Ph-DHA [a] 353 Ph-VHF [a] 470 218 min 1-00 [b] 365 1-11 [b] 476 140-160min to alteration of the complex diastereoisomeric mixture (as demonstrated to occur for ap reviously studied DHA derivative [18] ). This mixture moved within cycles towards an equilibrium as detected also from 1 HNMR spectroscopic experiments (see the Supporting Information, FigureS20 on changes of diastereoisomeric ratio in the 1 HNMR spectrum beforea nd after one light/heat cycle).…”
Section: Uv/vis Absorption Properties and Switchingstudiesmentioning
confidence: 98%